Pulsed laser in liquid grafting of gold nanoparticle–carbon support composites - Wilsey, Madeleine K.; Taseska, Teona; Lyu, Qishen; Cox, Connor P.; Müller, Astrid M. (Beilstein Journal of Nanotechnology, 2025)
We developed a novel pulsed laser-assisted process for the fabrication of advanced composites of nonequilibrium gold nanoparticles on carbon fiber paper supports. Our one-step process integrates the generation of nanoparticles with their surface attachment and solves longstanding nanoparticle adhesion and electrical contact issues. Irradiation of hydrophilic carbon fiber paper submerged in aqueous HAuCl4 solution by nanosecond laser pulses produced composites with uniform distribution of gold nanoparticles on carbon fibers, taking advantage of the high internal surface area of carbon fiber paper. The pulsed laser-grafted composites exhibited zero measurable charge transfer resistance between gold nanoparticles and the carbon support, leading to superior cathode performance over conventionally prepared electrodes for electrocatalytic hydrogen evolution in aqueous bicarbonate reduction.
Keywords: catalysis; composite; electroreduction; gold nanoparticles; impedance